2023
DOI: 10.1126/sciadv.adf6277
|View full text |Cite
|
Sign up to set email alerts
|

Lnc956 -TRIM28-HSP90B1 complex on replication forks promotes CMG helicase retention to ensure stem cell genomic stability and embryogenesis

Abstract: Replication stress is a major source of endogenous DNA damage. Despite the identification of numerous proteins on replication forks to modulate fork or replication machinery activities, it remains unexplored whether noncoding RNAs can localize on stalled forks and play critical regulatory roles. Here, we identify an uncharacterized long noncoding RNA NONMMUT028956 ( Lnc956 for short) predominantly expressed in mouse embryonic stem cells. Lnc956 is accumulated on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…To corroborate the presence of DNA damage in long-term cultured SPGs, we conducted gene expression analyses. Notably, both immunoblot assays ( Figure 5A ; Supplementary Figure S1A) and immunofluorescence staining ( Figure 5B ) revealed that levels of γH2AX, a marker of DNA DSBs ( Rogakou et al, 1998 ; Zhang et al, 2023 ), increased with culture. Alkaline comet assays, which quantify DNA breaks at the single-cell level, further verified the increase in DNA fragmentation ( Swain & Rao, 2011 ; Zhao et al, 2015 ) ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…To corroborate the presence of DNA damage in long-term cultured SPGs, we conducted gene expression analyses. Notably, both immunoblot assays ( Figure 5A ; Supplementary Figure S1A) and immunofluorescence staining ( Figure 5B ) revealed that levels of γH2AX, a marker of DNA DSBs ( Rogakou et al, 1998 ; Zhang et al, 2023 ), increased with culture. Alkaline comet assays, which quantify DNA breaks at the single-cell level, further verified the increase in DNA fragmentation ( Swain & Rao, 2011 ; Zhao et al, 2015 ) ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…PCNA and Histone H3 can be used as a fork-binding protein marker and mature chromatin marker, respectively. Please refer to Supplementary Figure 1A in our publication ( Zhang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA samples can be used either for qPCR analysis or RNA sequencing ( Figures 2 and 3 ). Please refer to Figure 1B , C, and D in our publication ( Zhang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations